Dead in the water - Johnson, Janice (Janice Kay); Mills & Boon Intrigue (Sydney, New South Wales : HarperCollins Publishers, 2021)
She saved an undercover agent's life...only to find herself fighting for her own. Claire Holland is terrified when a kayaking adventure accidentally intercepts a smuggling operation and her friend is gunned down. But before she can escape, Claire witnesses someone shot and fall overboard. Once she pulls him ashore, she discovers undercover DEA agent Adam Taylor is still alive but badly injured. Now they must navigate the dangerous coastal wilderness unseen. But has Claire saved a handsome hero's life... just to find her own in jeopardy? Mills & Boon Intrigue - Seek thrills. Solve crimes. Justice served.
General.
Keywords: Drug enforcement agents -- Fiction; Man-woman relationships -- Fiction; Private investigators -- Fiction; Contemporary romance; Fiction - Mystery & Detective - Police Procedural; Australian; Electronic books